Legal Position of Medical Negligence in Malaysia - Ahyuni Yunus; Rahman, Sufirman; Husni; Hatta, Muhammad; Djanggih, Hardianto (International Journal of Psychosocial Rehabilitation, 2020)
Doctors could not guarantee regarding recovery of their patient. Doctors can only work according to the knowledge they have. However, doctor’s failure to cure patients is often accused of doing medical negligence. The issue of medical negligence is not a new phenomenon in the doctoral profession, and even medical negligence has become a global issue. Although Malaysia is one of the few countries where medical emergencies occur, but the number of medical negligence increases each year. The Bolam v Friern Hospital Management Committee 1957 case has long been a measure of cases in medical negligence in Malaysia. However, after the Federal Court’s decision in the case of Foo Fio Na v Dr. Foo Sook Mun & Anor 2007, there was a change in the approach taken by a Malaysian court, which showed that the courts in Malaysia now no longer prioritize the Bolam test in medical negligence cases. In Civil Act 1956 and the Medical Act 1971, medical negligence is only regulated in a civil aspect so that the guilty physician will be punished to pay compensation to the patient. Generally, medical negligence cases are resolved through the court. However, it is difficult to prove the negligence done by the doctors and the length of time needed to take the case of medical negligence through the court has prompted physicians and patients to bring their case through the mediation forum.